2011
DOI: 10.1037/a0022885
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity does indeed promote attraction in live interaction.

Abstract: Does familiarity promote attraction? Prior research has generally suggested that it does, but a recent set of studies by Norton, Frost, and Ariely (2007) challenged that assumption. Instead, they found that more information about another person, when that information was randomly selected from lists of trait adjectives, using a trait evaluation paradigm, promoted perceptions of dissimilarity and, hence, disliking. The present research began with the assumption that natural social interaction involves contexts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
189
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 95 publications
14
189
1
Order By: Relevance
“…We could not agree moreyet, we also disagree strongly with the implication of their claim that their paradigms do in fact capture "natural social interaction." We would have guessed that if Reis et al (2011) were trying to examine natural social interactions, they would not have used a laboratory paradigm in which undergraduates alternated answering questions designed to promote relationship closeness (Study 1), or a paradigm in which undergraduates do not even meet face-to-face but chat via the Internet. Indeed, the task used in Study…”
Section: Are the Paradigms Representative Of Everyday Social Interactmentioning
confidence: 99%
See 2 more Smart Citations
“…We could not agree moreyet, we also disagree strongly with the implication of their claim that their paradigms do in fact capture "natural social interaction." We would have guessed that if Reis et al (2011) were trying to examine natural social interactions, they would not have used a laboratory paradigm in which undergraduates alternated answering questions designed to promote relationship closeness (Study 1), or a paradigm in which undergraduates do not even meet face-to-face but chat via the Internet. Indeed, the task used in Study…”
Section: Are the Paradigms Representative Of Everyday Social Interactmentioning
confidence: 99%
“…We were both pleased and displeased to see the recent article by Reis, Maniaci, Caprariello, Eastwick, and Finkel (2011) challenging the findings and account of our article (Norton, Frost, & Ariely, 2007)-pleased because it is always a compliment to have conducted research that irritated very smart people who we respect a great deal enough to want to follow-up on, but displeased because we believe that Reis et al have overstated the generalizability of their results and underreported other streams of literature that are in conflict with their account (reviewed below) and, even more, that Reis et al missed an opportunity to begin to construct an account that would integrate their findings, our findings, and the existing literature into a broader account of the link between knowledge and liking.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we examined a hypothetical or potential relationship, which is likely to be more uncertain than an established relationship. Hence, we expected that taste would create a subtle experience that uniquely affects perceptions of a novel or ambiguous relationship as compared to an established relationship.In addition, when making judgments in a romantic context, the judgments of nonestablished relationships may entail information processing that is relatively less elaborated and simpler (Reis, Maniaci, Caprariello, Eastwick, & Finkel, 2011), arguably because the target of evaluation is more psychologically distant than would be the case when evaluating an actual relationship (cf. Trope & Liberman, 2010).…”
mentioning
confidence: 99%
“…The theoretical foundation for this hypothesis is derived from recent evidence in the psychological literature. Reis et al (2011) found that individuals are more strongly attracted by individuals with whom they are more familiar. Translating this into the nancial context, this means that forecasts and recommendations of analysts working in the same country could appear more reliable, as these analysts might be perceived to be more familiar due to the same language or a similar background.…”
mentioning
confidence: 97%